2016
DOI: 10.1371/journal.pone.0157498
|View full text |Cite
|
Sign up to set email alerts
|

Field Performance of Bt Eggplants (Solanum melongena L.) in the Philippines: Cry1Ac Expression and Control of the Eggplant Fruit and Shoot Borer (Leucinodes orbonalis Guenée)

Abstract: Plants expressing Cry proteins from the bacterium, Bacillus thuringiensis (Bt), have become a major tactic for controlling insect pests in maize and cotton globally. However, there are few Bt vegetable crops. Eggplant (Solanum melongena) is a popular vegetable grown throughout Asia that is heavily treated with insecticides to control the eggplant fruit and shoot borer, Leucinodes orbonalis (EFSB). Herein we provide the first publicly available data on field performance in Asia of eggplant engineered to produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 27 publications
(28 reference statements)
2
20
0
Order By: Relevance
“…We reported previously that Bt eggplant demonstrated nearly 100% control of its major pest, EFSB, without the use of supplemental sprays [39]. Ex-ante studies for Bt eggplant in the Philippines [12, 13] indicated that producers and consumers would be benefited by Bt eggplant technology adoption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We reported previously that Bt eggplant demonstrated nearly 100% control of its major pest, EFSB, without the use of supplemental sprays [39]. Ex-ante studies for Bt eggplant in the Philippines [12, 13] indicated that producers and consumers would be benefited by Bt eggplant technology adoption.…”
Section: Discussionmentioning
confidence: 99%
“…[39]. The experimental materials used in the series of three Confined Field Trial (CFT) experiments are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While both the wild types TTB-7 and Pusa 992 showed maximum leaf damage above 45% (Fig. 2), transgenic events of cry2Aa (1, 4, 9, 10, 11, 13, 14,) and cry1AcF (19,22,25,26) showed leaf damage below 20%. However, one of the transgenics, event 7 of cry2Aa, showed about 22% leaf damage and the remaining events 5, 6, 8, 21, 23 and 24 showed leaf damage below 30%.…”
Section: Evaluation Of Transgenic Pigeonpea Under Soil Conditionsmentioning
confidence: 94%
“…Several studies have demonstrated successful field trials of transgenics developed for various traits, including insect resistance, through Bt ICPs. [20][21][22][23][24][25][26][27] However, there are no reports of evaluation of the reported pigeonpea transgenics outside laboratory conditions and under confined and contained soil conditions.…”
Section: Introductionmentioning
confidence: 99%